2021
DOI: 10.1111/jsr.13380
|View full text |Cite
|
Sign up to set email alerts
|

Social jetlag, a novel predictor for high cardiovascular risk in blue‐collar workers following permanent atypical work schedules

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…When analyzing social classes, we found a higher risk of obesity, diabetes, hypertension, MetS, atherogenic index, CVR, and BARD scoring system in blue-collar compared to white-collar workers. These results are consistent with other published studies that found that shift work is associated with an increased risk of CVD [ 55 ]. Socioeconomic and demographic differences are associated with an uneven distribution of health [ 56 ], in such a way that socioeconomic level presents an inverse association with the prevalence of MetS and diabetes mellitus, with a worse health status in the population with less purchasing power [ 57 ].…”
Section: Discussionsupporting
confidence: 94%
“…When analyzing social classes, we found a higher risk of obesity, diabetes, hypertension, MetS, atherogenic index, CVR, and BARD scoring system in blue-collar compared to white-collar workers. These results are consistent with other published studies that found that shift work is associated with an increased risk of CVD [ 55 ]. Socioeconomic and demographic differences are associated with an uneven distribution of health [ 56 ], in such a way that socioeconomic level presents an inverse association with the prevalence of MetS and diabetes mellitus, with a worse health status in the population with less purchasing power [ 57 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our body clocks systematically adjust to changes in photoperiod, but by suddenly changing the social clocks by one hour we abruptly change the phase angle between the time of arising and dawn [ 18 ]. Even without a change in time of arising caused by DST, many individuals experience circadian misalignment coupled with sleep loss [ 15 , 19 , 20 ], which has been associated with an increase in the risk of cardiovascular diseases [ 21 , 22 ]. Superimposed abrupt circadian misalignment caused by the spring DST transition might therefore pose additional cardiovascular burden on individuals with high levels of social jetlag, in primarily late chronotypes.…”
Section: Circadian Clock Chronotypes and Dstmentioning
confidence: 99%
“…Another form of chronic circadian misalignment is known as social jetlag, which is characterized by an ongoing discrepancy of an individual's sleep/wake cycle between workdays and free days. Importantly, several health consequences, including mood disorders, cardiac disease, obesity, metabolic syndrome, and type 2 diabetes mellitus, have been strongly linked to social jetlag ( Gamboa Madeira et al , 2021 ; Islam et al , 2020 ; Koopman et al , 2017 ; Roenneberg et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%